EFFECT OF ENRICHED SANJEEVANI AND AGNIHOTRA ON GROWTH, YIELD AND QUALITY OF BRINJAL (Solanum melongena L.) - Tripathy, Saswatik; Dutta, Avijit Kr. (Journal of Phytology, 2019)
Brinjal is a crop grown widely all over India and preferred by both rich and poor. The Chhotanagpur plateau of Jharkhand is famous for quality vegetable production and brinjal is very commonly grown in this region almost throughout the year. However, the most of the commercial growers using plant protection chemicals and synthetic fertilizers those are so expensive that poor farmers can’t afford. The extensive uses of agro-chemicals and synthetic fertilizers also reduce the quality of both the produce and the cultivated soil. In this context, an attempt has been made through the present investigation by growing different varieties of brinjal by adopting Vedic (Enriched Sanjeevani) Farming and Homa Induction (Agnihotra) techniques with their respective four non-chemical alternative growing approaches, viz. E1C1: Enriched Sanjeevani (1%), E1C2: Absolute Control (inherent fertility status of the experimental plot); E2C1: Enriched Sanjeevani (1%) + Homa Induction (Agnihotra), and E2C2: Only Homa Induction (Agnihotra). Five varieties of the crop, viz. V1: Swarna Pratibha; V2: Swarna Neelima; V3: Swarna Shakti; V4: Mukta Jhuri; V5: Long Green were grown with their four replications under four growing conditions and the Randomized Completed Block Design was adopted for field trials. Different growth, yield and quality attributing characters of the crop were taken into account and findings revealed that E2C1: Enriched Sanjeevani (1%) + Homa Induction (Agnihotra) was the most suitable growing condition for V2 (Swarna Neelima) with the maximum yield (72.37 t ha-1). Different growth and yield attributes of the crop varieties (especially in the case of V2: Swarna Neelima) were highly influenced by Enriched Sanjeevani (1%) + Homa Induction (Agnihotra) [E2C1] growing condition resulting higher benefit cost ratio of 6.78. Quality contributing attributes were also highly influenced by homa induction (Agnihotra), as a consequence, higher level of dry matter, TSS, and ascorbic acid contents were estimated from almost all samples collected from E2C1: Enriched Sanjeevani (1%) + Homa Induction (Agnihotra), and E2C2: Only Homa Induction (Agnihotra) growing conditions.